A novel set of symmetric methylene blue derivatives exhibits effective bacteria photokilling – a structure–response study. Issue 2 (14th November 2014) - Gollmer, Anita; Felgenträger, Ariane; Bäumler, Wolfgang; Maisch, Tim; Späth, Andreas
Abstract : This study focuses on the structure–response relationship of symmetrically substituted phenothiazinium dyes. Abstract : This study focuses on the structure–response relationship of symmetrically substituted phenothiazinium dyes. Four hydrophilic derivatives with the ability of additional hydrogen bonding (5, 6 ) or additional electrostatic interaction (3, 4 ) were synthesized, photophysically characterized and compared to the parent compound methylene blue (MB, 1 ) and a lipophilic derivative (2 ) without additional coordination sites. Derivative5 was most effective against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli reaching a maximum photodynamic efficacy of >5log10 steps (≥99.999%) of bacteria killing in 10 minutes (5 μM, 30 J cm −2 ) without inherent dark toxicity after one single treatment with the incoherent light source PDT1200 ( λ max = 660 nm, 50 mW cm −2 ). Interestingly, one derivative with two additional primary positive charges (3 ) showed selective killing of Escherichia coli (5 μM, 30 J cm −2, 4log10 steps inactivation (≥99.99%)) and no antimicrobial effect on Staphylococcus aureus . This might allow the development of a new generation of photosensitizers with higher antimicrobial efficacy and selectivity for future applications.